MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN PERBANKAN (STUDI PADA PERUSAHAAN PERBANKAN YANG TERCATAT DI BEI) - Iswanto Iswanto (Universitas muhammadiyah malang, 2014)
The purpose of this study is to determine the most influential ratio of CAMEL on bankruptcy of banking companies listed on the Stock Exchange. The other purpose is to predict bank bankruptcy. The result resesarch found that the ratios of CAMEL have a positive and significant effect in predicting bankruptcy of the banking company. The ratio of capital adequacy ratio (CAR) is accurate for predicting bank bankruptcy with a significance level of 0.014. It could be suggested that banks management should be pay more attention to the ratio of capital adequacy ratio (CAR) because it can provide a positive influence on the prediction of bank bankruptcy. Investors should be also pay more attention to the CAR when making a decision to minimize the risk. Further research should be consider other than CAMEL ratios, for example, aspects of compliance including Maximum Lending limit (LLL), reserve requirement (GWM), and Net Open Position (NOP). Keywords: Predicting Bankruptcy, CAMEL and CAR.